What Silent Pauses Can 'Tell' Us About the Storytelling Skills of Autistic Children: Relations Between Pausing, Language Skills and Executive Functions. - Peristeri, Eleni; Drakoulaki, Katerina; Boznou, Antonia; Nerantzini, Michaela; Gena, Angeliki; Lengeris, Angelos; Varlokosta, Spyridoula (Journal of Autism & Developmental Disorders, 2025)
Silent pauses may serve communicative purposes such as demarcating boundaries between discourse units in language production. Previous research has shown that autistic children differ in their pausing behavior from typically-developing (TD) peers, however, the factors behind this difference remain underexplored. The current study was aimed at comparing the use of silent pauses in the narrative production of autistic children and age-matched TD children, and also to identify possible relations between pausing behavior and the children's language and executive function abilities. According to the study's findings, the autistic children did not differ from their TD peers in the use of grammatical pauses, however, the former tended to produce significantly less syntactically complex narratives than the TD group, which increased the likelihood that the autistic group would pause appropriately at phrasal boundaries. Though we have found low rates of ungrammatical silent pauses and omitted pauses in obligatory discourse contexts across both groups, autistic children with lower cognitive flexibility tended to use more ungrammatical pauses than their peers with higher cognitive flexibility scores. Also, the autistic group tended to omit obligatory silent pauses more often as their narration became more complex. The results demonstrate that syntactic complexity in narrative production modulated autistic children's pausing behavior, and that structurally simple narrations boosted the autistic group's appropriate use of grammatical pauses. The overall findings also demonstrate the importance of studying silent pauses in the narrative discourse of autistic children, and also highlight the links between silent pauses and the children's syntactic and cognitive skills.